Aeroelastic dynamic stall computations of a double-swept blade in a four-bladed rotor configuration - Babij, G. (My University, 2022)
Innovative helicopter rotor blades with a combined forward-backward double-sweep at the outer part of the blade enable a reduction in noise emission and enhance the overall performance of a rotor. In this context, the influence of the aeroelastic behaviour in connection with the dynamic stall phenomenon is of great importance. It is accompanied by large aerodynamic load peaks, primarily seen in the lift and the pitching moment, impacting the structural integrity of the blades and adjacent control components. Double-swept model rotor blades were developed and investigated experimentally at the DLR Goettingen regarding the dynamic stall behaviour in a four-bladed rotor configuration at the Rotor Test Facility Goettingen. Due to an axial inflow to the rotor disc a sinusoidal variation in pitch angle is introduced to trigger the dynamic stall behaviour once per revolution. The experimental investigations were accompanied by aeroelastic as well as purely aerodynamic numerical simulations which are the main focus in this study. In case of the aeroelastic simulations, a tight coupling scheme was implemented to perform the data exchange between the inhouse CFD solver TAU and the commercial software Simpack as solver for multibody systems with flexible bodies in each time step. Six test cases with a rotational frequency of 23.6 Hz are presented comprising three with solely collective pitch angle and three with a superposed cyclic variation in pitch angle in order to introduce and strengthen the dynamic stall behaviour stepwise for the investigated rotor configuration. As a result, differences arise in the aerodynamic loads between both blade modelling approaches. They are elaborated in order to draw conclusions about the dynamic stall behaviour under consideration of elasticity in the blade modelling.